FEATURES OF PREPARATION AND CONDUCTING STABILIZATION ACTIONS BY MILITARY FORMATIONS WITH LAW ENFORCEMENT FUNCTIONS OF NORTH ATLANTIC ALLIANCE COUNTRIES - Adamchuk, Maksym; Butuzov, Vitaliy; Luhovskyi, Ihor; Voronin, Andriy (Honor and Law, 2023)
The article explores the essence and content of the preparation and conduct of stabilization actions by military formations with law enforcement functions according to NATO standards. It discusses the activities of the NATO Centres of Excellence, substantiates the concepts, essence, and content of stabilization actions by the security forces of Ukraine. The NATO Advanced Civil-Military Interaction Training Center for Enhancing Qualifications in Law Enforcement Stabilization Actions serves as an international coordination and knowledge hub for the community of interests in the field of stabilization actions with law enforcement characteristics. Currently, the organization consists of the following structures specialized in the described activities: Carabinieri Corps of Italy, Czech Military Police, French Gendarmerie, Greek Army, Polish Military Gendarmerie, Romanian Gendarmerie, Spanish Civil Guard, Royal Netherlands Marechaussee, and Turkish Gendarmerie. The center examines the concept of stabilization actions with law enforcement characteristics applied by NATO member countries in unstable regions (states) in all types of conflicts, ranging from peacetime to high-intensity conflicts. The spectrum of conflicts encompasses four main types of campaigns in which stabilization actions are conducted. Typically, these actions occur both during the initial stages and throughout armed conflicts (combat operations), as well as after their conclusion. The article introduces the definition of law enforcement stabilization actions, which has not been previously reflected in the normative-legal framework of the security sector components of Ukraine. The implementation of a comprehensive set of law enforcement stabilization actions will play a crucial role in the post-war period during the restoration of constitutional order and territorial integrity of Ukraine, which have been affected by Russian occupation.